2014
DOI: 10.3345/kjp.2014.57.10.461
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled iloprost for the treatment of patient with Fontan circulation

Abstract: Decreased exercise capacity after Fontan surgery is relatively common and the failure of the Fontan state gradually increases with age. However, there is no further treatment for patients with Fontan circulation. Pulmonary vasodilation therapy is an effective method to solve this problem because pulmonary vascular resistance is a major factor of the Fontan problem. Inhaled iloprost is a chemically stable prostacyclin analogue and a potent pulmonary vasodilator. We experienced two cases of Fontan patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Reducing pulmonary vascular resistance improves blood flow across the pulmonary capillaries, which results in a reduced central venous pressure and improved cardiac output. Various pharmacological agents have shown to reduce pulmonary artery pressures such as endothelial receptor antagonists [ 5 ] prostanoids [ 6 ] and phosphodiesterase type 5 inhibitors [ 7 ]. This case report involves the first use of macitentan (an endothelin-receptor antagonist) in a patient with a Fontan circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing pulmonary vascular resistance improves blood flow across the pulmonary capillaries, which results in a reduced central venous pressure and improved cardiac output. Various pharmacological agents have shown to reduce pulmonary artery pressures such as endothelial receptor antagonists [ 5 ] prostanoids [ 6 ] and phosphodiesterase type 5 inhibitors [ 7 ]. This case report involves the first use of macitentan (an endothelin-receptor antagonist) in a patient with a Fontan circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Prostanoid, E-type 1 prostaglandin (PGE1), is commonly used in HLHS neonates prior to Norwood palliation to maintain patency of the ductus arteriosus [ 51 , 52 , 53 ]. HLHS patients are dependent on a patent ductus arteriosus to provide systemic blood flow, due to severe obstruction of the left ventricular outflow tract.…”
Section: Current Hlhs Heart Failure Therapiesmentioning
confidence: 99%
“…PGE1 dilates the ductus arteriosus as a postnatal therapeutic to maintain the right to left shunting of systemic blood flow prior to surgical intervention. Prostanoid use in older SV patients, particularly post-Fontan is rare; however, several small studies have looked at inhaled iloprost in patients with Fontan circulation and found improvement in peak oxygen pulse and maximum VO2, as well as improved exercise capacity and cardiac output [ 52 , 53 ].…”
Section: Current Hlhs Heart Failure Therapiesmentioning
confidence: 99%
“…The role of prostacyclines has been investigated in only two trials, which found beneficial effects of inhaled iloprost on symptoms and exercise performance [ 86 , 87 ].…”
Section: Group 1 Ph ( Table 1 )mentioning
confidence: 99%